Influence of vacancy defects on the damage mechanics of graphene nanoribbons. (January 2017) - Zhang, Ji; Ragab, Tarek; Basaran, Cemal
Using molecular dynamics simulations, graphene nanoribbons with armchair chirality were subjected to displacement-controlled uniaxial tension until complete fracture at 300 K in order to understand their damage mechanics. Graphene nanoribbons with and without a vacancy defect were simulated to compare the effect of the defect on the fracture behavior. Simulations were performed for graphene nanoribbons with lengths ranging from 2.5 to 15 nm. The stress–strain curve of each case is reported, and the influence of defect on the material properties is discussed. For each sample, damage mechanics types were observed and discussed. Results show a negligible effect of the single vacancy defect on the ultimate strength of the graphene nanoribbon. However, having a single vacancy defect does influence the failure strain, as well as the damage mechanics past the ultimate stress point.